Combined impact of drought and land use changes on water resources in the Tabular Middle Atlas, Morocco - El-Bouhali, Abdelaziz; Amyay, Mhamed; El Ouazani Ech-Chahdi, Khadija (Revista de Estudios Andaluces, 2024)
The quantitative degradation of water resources in the Tabular Middle Atlas is linked to climate and changes in agricultural practices. The relationship between these variables is identified through the analysis of hydroclimatic data, fieldwork, and the processing of Landsat satellite images in two representative sectors of the Middle Atlas. Interviews with local populations and piezometric measurements performed in the Guigou depression show that the groundwater table has dropped from a few meters deep to over 45 meters in several locations. Additionally, monitoring of the surface water area of Aoua lake between September 1984 and September 2022 from satellite images indicates remarkable variations, with periods of prolonged drying. The critical situation of water resources in this sector of Morocco is explained by the recurrence of drought periods of varying severity, increasing temperatures, and the progressive extension of irrigated areas across the depressions. In three decades, irrigated areas have multiplied by more than five in the Guigou depression and by more than three in the Imouzzer-Aoua depressions. Changes in climatic parameters associated with modifications in agricultural practices have strongly influenced water resources in the Tabular Middle Atlas.